Pilot study of mitochondrial bioenergetics in subjects with acute porphyrias - Dixon, Natalia; Li, Ting; Marion, Brandon; Faust, Denise; Dozier, Stephen; Molina, Anthony; Rudnick, Sean; Bonkovsky, Herbert L. (Molecular genetics and metabolism, 2019)
The acute porphyrias are characterized by defects in heme synthesis, particularly in the liver. In some affected patients, there occurs a critical deficiency in a regulatory heme pool within hepatocytes that leads to up-regulation of 5-aminolevulinic acid [ALA] synthase-1, which is the first and normally rate-controlling enzyme in the pathway. In earlier work, we described defects in mitochondrial functions in cultured skin fibroblasts from patients with acute intermittent porphyria [AIP]. Others described defects in livers of murine models of AIP. Here, we explored mitochondrial energetics in peripheral blood mononuclear cells [PBMCs] and platelets in persons with AIP and hereditary coproporphyria [HCP]. Our hypotheses were that there are deficits in bioenergetic capacity in acute porphyrias and that subjects with more severe acute porphyria have more pronounced reductions in mitochondrial oxygen consumption rates [OCR]. We studied 17 subjects with acute hepatic porphyrias, 14 with classical AIP, one with severe AIP due to homozygous deficiency of hydroxymethylbilane synthase [HMBS], 2 with HCP, and 5 non-porphyric controls. We collected peripheral blood, isolated PBMCs, which we assayed either immediately or after frozen storage [80C] for up to 14 days. Using Seahorse XF-24-3, we measured OCR in the presence of glucose + pyruvate under basal condition, and after additions of oligomycin, carbonylcyanide p-trifluoromethoxyphenylhydrazone [FCCP], and antimycin+rotenone. Most subjects [13/17, 76%] were female. Subjects with moderate/severe symptoms associated with acute porphyria had significantly lower basal and maximal-OCR than those with no/mild symptoms who were the same as controls. We observed significant inverse correlation between urinary porphobilinogen [PBG] excretion and OCR. The subject with homozygous AIP had a much lower-OCR than his asymptomatic parents. Results support the hypothesis that active acute hepatic porphyria is characterized by a deficiency in mitochondrial function that is detectable in PBMCs, suggesting that limitations in electron transport and ATP production exist in such individuals.